Reflections of social change in Turkish society in the 1970s based on the story of Yokuşa Akan Sular [1970’lerde Türk Toplumundaki Sosyal Değişimin Yokuşa Akan Sular Hikâyesindeki Akisleri] - (:unkn) unknown (Ahmet Yesevi University, 2016)
In his book, Yokuşa Akan Sular, Mustafa Kutlu addresses the conflicts faced by poverty-striken people who migrated from various parts of Anatolia to İstanbul in the time period, and their ongoing struggle for survival. The book which demonstrates the character of a frame story,presents a dramatization of the changing values and psychological traumas of the people who migrated to metropoles within the context of an exploitatory regime. Although elements of social change in Yokuşa Akan Sular have been touched upon in previous works on Mustafa Kutlu, to date the social change aspect has not been examined thoroughly. Therefore, this paper will investigate how social change in Turkish society in the 1970s was treated in Yokuşa Akan Sular drawing upon existing sociological research about the time period and considering the findings of previous studies. © 2016, Ahmet Yesevi University. All rights reserved.
Keywords: Alienation; Mustafa Kutlu; Short story; Social change; Struggle for existence; Yokuşa Akan Sular